CASE REPORT OF ADENOID CYSTIC CARCINOMA OF THE BREAST: A RARE LESION WITH FAVORABLE PROGNOSIS - Araujo, Juliana Lopes de Aguiar; Sousa, Ubiratan Wagner de; Sousa, Wender Batista de; Almeida, Iris Maria Rodrigues de Andrade; Lira, Luisa Gurgel de (Mastology, 2020)
Introduction: Adenoid cystic carcinoma (ACC) is a rare type of breast tumor – less than 0.1% of breast malignancies. Usually, ACC is triple-negative, with lymph node involvement not exceeding 2%, and metastases are uncommon. When localized, the disease is indolent with an excellent prognosis. Objective: To report a case of ACC of the breast and pro-vide data for the medical literature. Method/Case report: J.S.M.S., 44 years old, had a 1 cm nodule in the right breast (RB) and free axillae. Mammography (MMG) showed focal asymmetry in the upper outer quadrant (UOQ) and BI-RADS 0. Ultrasound (US) revealed a solid, circumscribed, periareolar lesion with areas of cystic degeneration, 1.2 cm, BI-RADS 3. Fine-needle aspiration biopsy (FNAB) suggested fibroadenoma. Lesion resection led to the diagnosis of ACC, histological grade 1 (HG1), nuclear grade 1 (NG1), with associated ductal carcinoma in situ (DCIS), and sentinel lymph node with no neoplasia. Immunohistochemistry (IHC) revealed estrogen receptor-negative (ER-), progesterone receptor-negative (PR-), HER2 negative (HER2-), and Ki67 10%. Staging had no evidence of distant disease. The patient did not receive chemothe-rapy (CT) but underwent 18 sessions of radiotherapy (RT) in the breast with a boost to the tumor bed. She remains dise-ase-free at 8 months of follow-up. Results/Discussion: ACC has low malignant potential with histology similar to that of primary ACC of the salivary gland (which is aggressive); in the breast, it represents 0.058% of all ACC cases. It is more common in Caucasian women aged 60 to 70 years and usually subareolar (approximately 50% of cases). Imaging tests are nonspecific. ACC has lymph node involvement in about 2% of cases. Histology shows epithelial and myoepithelial cells distributed in the classic tubular or cribriform architecture. IHC reveals epithelial cells positive for CD117 and myoepi-thelial cells positive for smooth muscle actin, calponin, and p63. ACC of the breast expresses proto-oncogene c-KIT and a chromosomal translocation similar to its salivary counterpart: t (6; 9) (q22-23; p23-24). Treatment consists of surgery with free margins. Axillary dissection, CT, and RT have a questionable role due to the indolent course of the disease. Until now, small studies have not suggested a benefit in overall survival when adding adjuvant CT. Although triple-negative, its prognosis is favorable. Local recurrence is approximately 3–18%, and 10-year survival is above 90%. Conclusion: The rarity of these tumors and their favorable course raise questions about the best treatment for ACC. The benefit of axillary dissection, CT, or RT remains unknown because the prognosis seems very favorable with only surgery, despite its triple–negative status. Further studies are necessary to adopt the optimal strategy for these tumors.